Triglyceride-Glucose Index Predicts Adverse Events in Patients with Acute Coronary Syndrome: A Meta-Analysis of Cohort Studies - Li, Juying; Ren, Ling; Chang, Cheng; Luo, Lin (Hormone and Metabolic Research, 2021)
The triglyceride-glucose (TyG) index, a recently proposed indicator for insulin resistance, has been related with cardiovascular risks. We aimed to summarize the association between TyG index and incidence of major adverse cardiovascular events (MACEs) in patients with acute coronary syndrome (ACS). Cohort studies demonstrating the association between TyG index and incidence of MACEs in ACS patients with multivariate adjusted analyses were identified by search of PubMed, Embase, and Web of Science databases. A random-effekt model incorporating the heterogeneity was applied to pool the results. Eight cohort studies with 19 611 participants were included. Results showed that compared to those with the lowest category of TyG index, ACS patients with the highest category of TyG index were independently associated with higher risk of MACEs [risk ratio (RR): 1.94, 95% confidence interval (CI): 1.47–2.56, I2=85%, p <0.001). Subgroup analyses showed consistent results in patients with ST-segment elevated myocardial infarction or non-ST segment elevated ACS, in patients with or without diabetes, and in patients after percutaneous coronary intervention. Results were consistent in studies with TyG index analyzed as continuous variable (RR for per standard deviation increment of TyG index: 1.59, 95% CI: 1.38–1.83, I2=24%, p <0.001). In conclusion, higher TyG index may be independently associated with higher incidence of MACEs in patients with ACS.
Keywords: triglyceride-glucose index; insulin resistance; acute coronary syndrome; major adverse cardiovascular events; meta-analysis